2017
DOI: 10.22159/ijcpr.2017v9i6.23427
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Study of Drug Utilization Pattern of Anti-Epileptic Drugs and Their Adverse Effects in a Tertiary Care Hospital

Abstract: Objective: Epilepsy or seizure disorder is a common neurologic disorder in the pediatric age group and occurs with a frequency of 4-6 cases per thousand children. Epilepsy, particularly childhood epilepsy, remains a challenge to treat. The management of epilepsy is primarily based on the use of anti-epileptic drugs. Surgery and diet therapy are the other modes of treating childhood seizures. To get an insight into the utilization pattern of anti-epileptic drugs (AEDs) used in pediatric seizures.Methods: This p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Sodium valproate was the mainstay of treatment in pediatric seizures. Side effects were minimal(10). In the present study, the most commonly used Antiepileptic drug was also Sodium valproate.…”
mentioning
confidence: 63%
“…Sodium valproate was the mainstay of treatment in pediatric seizures. Side effects were minimal(10). In the present study, the most commonly used Antiepileptic drug was also Sodium valproate.…”
mentioning
confidence: 63%
“…Generalized tonic–clonic seizure (GTCS) was the most common form of seizure (48.35%) observed in our study. A majority of previous clinical studies have shown the dominance of this seizure type in children while a study conducted by Patel et al .…”
Section: Discussionmentioning
confidence: 97%
“…Generally, monotherapy is the first line of treatment because it has few drug interactions and side effects, tolerability, increased compliance, and quality of life. [5][6][7][8][9]…”
Section: Introductionmentioning
confidence: 99%